Investigating the role of KARS in lung adenocarcinoma via single-cell RNA sequencing - Huafang Hu; Yan Zhong; Guangbiao Li; Ru Deng; Jingfu Lin; Wenkun Wu; Yonghong Li (Discover Oncology)
Abstract Objective Lung Adenocarcinoma (LUAD) is one of the leading causes to cancer-related deaths worldwide and exhibited extensive molecular diversity in its cellular components. In summary, this study examined the expression and function of KARS in various LUAD cell populations using single-cell RNA sequencing (scRNA-seq) to identify its prognostic value as well as potential implications for therapy. Methods All datasets related to this study were analyzed in previous published studies, which was downloaded from The Cancer Genome Atlas (TCGA), Genotype-Tissue Expression(GTEx) project and Gene Expression Omnibus (GEO). We subsequently sought to analyze the association between either clinically tumorigenic or low survival-grade KARS expression, respectively with varied clinicopathological features and all patients OS. Verification of KARS expression was performed by in vitro RT-PCR. Results Our investigation found that KARS expression was markedly elevated in LUAD tissue samples compared to normal controls. Genomic analysis indicated a robust association between increased copy number of the KARS gene and its overexpression. The upregulation of KARS was also correlated with distinct genetic mutations and a higher mutational load in LUAD. The heightened activity of KARS was implicated in LUAD progression. Furthermore, our research indicated a significant interplay between KARS's role in LUAD and the tumor's immune microenvironment, along with various dimensions of the tumor immunology landscape. Comprehensive assessments of immune cell populations within the tumor microenvironment uncovered a pronounced link between heightened immune responses and the presence of specific immune cell types. KARS expression in A549 cell line was higher than in the 16HBE cell line. Conclusion Utilizing single-cell omics technologies, this research offers a detailed perspective on the role of KARS in LUAD, highlighting its potential as a prognostic biomarker and a candidate for tailored therapeutic intervention. Future research should probe possible therapeutic strategies that could target KARS in a pathologically relevant manner.